The 9th International Conference "Environmental Engineering 2014" 2014
DOI: 10.3846/enviro.2014.150
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Vertical Traffic Calming Measures in Impacts on Road Safety and Environment in Lithuania State Roads

Abstract: Several years after implementation of vertical traffic calming measures on roads, crossing cities and settlements, for the first time in Lithuania the research was carried out to determine their effect on the change in the number of accidents, their severity and noise within the operation zone of speed humps, raised pedestrian crossings and speed bumps. The paper present research methodology and analysis of results of vertical traffic calming influence to the road safety and environment in Lithuania roads. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Speed humps have the ability to reduce the injury accidents about 41% according to Jateikienė, et al [14]. Similar findings were obtained by Čygaitė [15] who examined the effect of speed humps in Lithuania. The later suggested that number of killed people were reduced by 100%.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Speed humps have the ability to reduce the injury accidents about 41% according to Jateikienė, et al [14]. Similar findings were obtained by Čygaitė [15] who examined the effect of speed humps in Lithuania. The later suggested that number of killed people were reduced by 100%.…”
Section: Introductionsupporting
confidence: 72%
“…Chen et al [16] suggested that the use of speed humps in New York City reduced the fatal and injury accidents by 33%. Based on data from Iraq U-turn sites, Al-Obaedi [15] reported that speed humps reduced the merging time by more than 50%. Shwaly et al [17], based on a questionnaire in Egypt, found that both vehicle speeds and accident rates significantly reduced as the effect of speed humps.…”
Section: Introductionmentioning
confidence: 99%
“…Where distance between two vertical traffic calming measures is 200-400 m, vehicles have time to accelerate and to reach a speed even 10 km/h higher than the speed limit. Taking into consideration the results of their previous studies [25,26] and the review of foreign legal acts and studies, the authors suggest new recommendations related to the distance between speed calming measures. The currently valid distances in Lithuania (R ISEP 10) and distances recommended by the authors are given in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Other speed related efficiency parameters are 85 th percentile speed, standard deviation of longitudinal acceleration and deceleration, percentage of drivers exceeding the speed limit, the highest speeds, 10 mph pace (Ariën et al 2013(Ariën et al , 2014Corkle et al 2002;Mountain et al 2005). Among other commonly used TCM efficiency parameters are reduction of traffic volume, change in the number of fatal and injury accidents, traffic noise level, vehicle emission and public health impact (Čygaitė et al 2014;Huang, Cynecki 2001;Lee et al 2013). Some authors measure TCM efficiency as a delay per TCM during emergency transport (Berthod 2011), or delay time for crossing the road (Garrod et al 2002), cost of traffic calming project and maintenance costs (Garrod et al 2002, Langdon 2003.…”
Section: Unified Methodology For Estimating Efficiency Of Traffic Calmentioning
confidence: 99%
“…Other authors estimate such effeciency parameters as private expenditures in fuel and vehicle maintenance (Jazcilevich et al 2015), impact on public transport (Banister 2009) and cyclists (Pinkerton et al 2013). Literature analysis shows that public acceptance has become an important TCM efficiency component (Čygaitė et al 2014;El-Basyouny, El-Bassiouni 2013;Garrod et al 2002). Nevertheless the most common efficiency parameters of TCM are connected to speed, traffic volume and number of accidents.…”
Section: Unified Methodology For Estimating Efficiency Of Traffic Calmentioning
confidence: 99%